Formative evaluation of residents from the residents and their attending Points of views - Vahidd Mirzai; Ali Akbar Haghdoost; Ali Akbar Haghdoost; Fereydon Azizi (Kerman University of Medical Sciences, 2014)
Background & Objective: Formative tests during the course means when the teacher is still teaching skills The present study aimed to identify the strengths and weaknesses of students and guide them   Methods: In this crosssectional study seven universities were selected using cluster random sampling in different type and geographical locations Using a simple random sampling out of 98 residents 12 attending who were enrolled in the study Data collection was done by questionnaire and interviewing forms Data were analyzed using descriptive and inferential statistics   Results: In the residents view in six items which were assessed in the questionnaire taking history physical presence of the residents clinical analysis and on time presence on the bedside were the highest items evaluated From the attending point views taking history timely presence of the residents diagnosis methods and exact physical exams were the most items being evaluated respectively There were significant differences between evaluated universities on the items such as timely presence on the bedsides and following cost effective treatments and patients care   Conclusion: Relevant authorities should monitor the implementation of the current methods of teaching to achieve maximum benefits and not just evaluate items like physical presence It seems respecting for patients privacy and ethical obligations must also be considered